2021
DOI: 10.1016/j.jare.2020.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships study of isothiocyanates for H2S releasing properties: 3-Pyridyl-isothiocyanate as a new promising cardioprotective agent

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Numerous in vitro , ex vivo and in vivo studies demonstrated the vasoactive role of H 2 S, confirming the hypothesis that H 2 S importantly contributes to the regulation of vascular tone [22] , [23] . In fact, like NO, H 2 S assures the maintenance of vascular homeostasis by the regulation of the complex balance of several components, including vasodilation responses as widely demonstrated for molecules able to release H 2 S [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] .…”
Section: Hydrogen Sulfide and Hypertension-related Endothelial Dysfunmentioning
confidence: 99%
“…Numerous in vitro , ex vivo and in vivo studies demonstrated the vasoactive role of H 2 S, confirming the hypothesis that H 2 S importantly contributes to the regulation of vascular tone [22] , [23] . In fact, like NO, H 2 S assures the maintenance of vascular homeostasis by the regulation of the complex balance of several components, including vasodilation responses as widely demonstrated for molecules able to release H 2 S [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] .…”
Section: Hydrogen Sulfide and Hypertension-related Endothelial Dysfunmentioning
confidence: 99%
“…Nrf2 is a nuclear factor responsible for promoting the expression of multiple antioxidant genes and preventing oxidative damage. Such a mechanism of action has been described also for synthetic isothiocyanates whose H 2 S donor profile has been widely described (Citi, Corvino, et al, 2020;Citi et al, 2014Citi et al, , 2019Martelli, Piragine, et al, 2020;Martelli et al, 2014;Prawan et al, 2009;Sestito, Daniele, et al, 2019;Sestito, Pruccoli, et al, 2019;Testai et al, 2016). Anethole dithiolethione, another H 2 S donor, has been widely used as H 2 S donor or as a moiety for the development of H 2 S-releasing hybrid drugs, including non-steroidal anti-inflammatory agents, such as H 2 S-aspirin and H 2 S-diclofenac.…”
Section: H 2 S In Inflammatory Lung Diseasesmentioning
confidence: 96%
“…Thus, in order to obtain effective H 2 S donors with controllable release rates, a series of N-(benzoylthio)benzamides [ 49 ], acyl perthiols [ 50 , 51 ], arylthioamides [ 52 ], 1,2,4-thiadiazolidin-3,5-diones [ 53 ], iminothioethers [ 54 ], mercaptopyruvate [ 55 ], dithioates [ 56 ], isothiocyanate [ 57 , 58 ], and thiocarbamates [ 59 ] were developed and evaluated for their H 2 S-releasing properties.…”
Section: H 2 S Donorsmentioning
confidence: 99%
“…Noteworthy, 4-carboxyphenyl-isothiocyanate (4-CPI) and 3-pyridyl-isothiocyanate ( Figure S20 ) exhibited cardioprotective effects against I/R injury, reducing myocardial contractility, ventricular arrhythmias, and oxidative stress [ 58 , 151 ].…”
Section: H 2 S Donorsmentioning
confidence: 99%